Occupational Segregation and the (Mis)allocation of Talent. (28th December 2017) - Pothier, David
Abstract: In this paper, I study how occupational segregation affects the allocation of talent in a competitive labour market. I propose a model of occupational choice in which heterogeneous workers must rely on their social contacts to acquire job‐vacancy information. While occupational segregation implies benefits in terms of job‐finding probability, it also leads to allocative inefficiencies. Efficient and equilibrium outcomes differ due to a network externality that leads workers to segregate too little, and a pecuniary externality that leads workers to segregate too much. Which effect dominates depends on the elasticity of wages to changes in the degree of occupational segregation.